2012
DOI: 10.1371/journal.pone.0030281
|View full text |Cite
|
Sign up to set email alerts
|

Are Tuberculosis Patients in a Tertiary Care Hospital in Hyderabad, India Being Managed According to National Guidelines?

Abstract: SettingA tertiary health care facility (Government General and Chest hospital) in Hyderabad, India.ObjectivesTo assess a) the extent of compliance of specialists to standardized national (RNTCP) tuberculosis management guidelines and b) if patients on discharge from hospital were being appropriately linked up with peripheral health facilities for continuation of anti-Tuberculosis (TB) treatment.MethodsA descriptive study using routine programme data and involving all TB patients admitted to inpatient care from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Two studies assessed practices among in-patients in tertiary care hospital settings and found very high rates of adherence to guidelines. 39,41 In contrast, one study assessed the correctness of both the combination of drugs and the dosages in the out-patient setting and found that in most cases neither the dosages nor the drug combinations were in line with ISTC recommendations. 42 …”
Section: Resultsmentioning
confidence: 99%
“…Two studies assessed practices among in-patients in tertiary care hospital settings and found very high rates of adherence to guidelines. 39,41 In contrast, one study assessed the correctness of both the combination of drugs and the dosages in the out-patient setting and found that in most cases neither the dosages nor the drug combinations were in line with ISTC recommendations. 42 …”
Section: Resultsmentioning
confidence: 99%
“…Few studies have assessed the successful linkage for continuing anti-TB treatment after referral from medical colleges in India, where a large proportion of all TB patients are diagnosed and referred. [12] In the present study, only 13 (0.9%) patients were started on treatment at the DOTS center of the medical colleges and majority (87.6%) of the TB patients diagnosed were referred to start and continue treatment at the PHIs. Among those thirteen patients, who were started on treatment at the DOTS centre of medical colleges, seven patients were offered non-DOTS or non-RNTCP drug regimens.…”
Section: Discussionmentioning
confidence: 55%
“…Among 138 MDR-TB patients hospitalized, only seven (5%) had unfavorable outcomes (death or a worsened clinical condition). This proportion is lower compared to a study that included drug-susceptible and drug-resistant TB patients admitted to a tertiary hospital in India (14%) [ 15 ].…”
Section: Discussionmentioning
confidence: 76%